Zika virus induces monocyte recruitment in the immunocompetent adult brain driving chronic inflammation - Garcia Diaz, Josefina; Park, Soo-Jeung; Legouez, Lou; Comlekoglu, Tina; Beck, Ashley; Kuan, Chia-Yi; Hahn, Young S. (Frontiers in Immunology, 2025)
Zika virus (ZIKV) is a neurotropic pathogen linked to neuropathogenesis in adults, causing conditions such as Guillain-Barré syndrome (GBS) and fatal encephalitis. Intracranial injection of virus in immunocompromised mice have shown neuroinflammation and subsequent brain damage. However, the mechanisms underlying ZIKV-induced neuroinflammation in immunocompetent adult mice via peripheral infection remain unclear. To investigate this, we utilized a murine model of ZIKV infection via footpad injection. Our findings reveal that acute ZIKV infection at 4 days post-infection (4 dpi) induces significant apoptosis and neuroinflammation in the adult brain, persisting up to 28 dpi. Notably, ZIKV infection triggers apoptosis in the hippocampus and cortex—key regions involved in memory—and induces early immune cell infiltration. Additionally, microglial activation occurs following infection at 7 dpi, with viral RNA detected in the brain. Bulk RNA sequencing of the hippocampus at 28 dpi further reveals the activation of inflammatory pathways, underscoring the prolonged neuroinflammatory response in the infected brain. Microglial activation is likely driven by infiltrating monocytes, as inhibiting monocyte recruitment reduced the expression of microglial activation genes. These results suggest that targeting monocyte-induced inflammatory mediators could be potential therapeutic interventions for ZIKV.